Book Review: Big Brown: The untold story of UPS by Greg Niemann. (1st December 2008) - Lu, Angela Cheng-Jui
Big Brown: The untold story of UPS, by Greg Niemann. San Francisco, CA, John Wiley & Sons, Inc., 2007. 245pp. ISBN 978-0-7879-9402-0